Deciphering complexity: TULP1 variants linked to an atypical retinal dystrophy phenotype - Esteve-Garcia, Anna; Cobos, Estefania; Sau, Cristina; Padró-Miquel, Ariadna; Català-Mora, Jaume; Barberán-Martínez, Pilar; Millán, José M.; García-García, Gema; Aguilera, Cinthia (Frontiers in Genetics, 2024)
Introduction:TULP1 exemplifies the remarkable clinical and genetic heterogeneity observed in inherited retinal dystrophies. Our research describes the clinical and molecular characteristics of a patient manifesting an atypical retinal dystrophy pattern, marked by the identification of both a previously unreported and a rarely encountered TULP1 variant. Methods: Whole-exome sequencing was performed to identify potential causative variants. The pathogenicity of the identified TULP1 variants was evaluated through in silico predictors and a minigene splice assay, specifically designed to assess the effect of the unreported TULP1 variant. Results: We identified two TULP1 gene variants in a patient exhibiting unusual and symmetrical alterations in both retinas, characterized by an increase in autofluorescence along the distribution of retinal vessels. These variants included a known rare missense variant, c.1376T>C, and a novel splice site variant, c.822G>T. For the latter variant (c.822G>T), we conducted a minigene splice assay that demonstrated the incorporation of a premature stop codon. This finding suggests a likely activation of the nonsense-mediated mRNA decay mechanism, ultimately resulting in the absence of protein production from this allele. Segregation analysis confirmed that these variants were in trans. Discussion: Our data support that individuals with biallelic TULP1 variants may present with a unique pattern of macular degeneration and periarteriolar vascular pigmentation. This study highlights the importance of further clinical and molecular characterization of TULP1 variants to elucidate genotype–phenotype correlations in the context of inherited retinal dystrophies.